2008
DOI: 10.1002/gcc.20580
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of miR‐106a predicts survival in human colon cancer patients

Abstract: MicroRNAs (miRNAs) are noncoding RNAs that regulate expression of target mRNAs and are controlled by tumor suppressors and oncogenes. Altered expression of specific miRNAs in several tumor types and its association with poor prognosis parameters have been reported. Fewer data are available on its impact on patients' survival. We studied the impact of the expression of miR-17-5p, miR-106a, and miR-126 on survival and its correlation with the levels of their target mRNAs and host gene and TP53 alterations. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
163
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(184 citation statements)
references
References 51 publications
16
163
1
4
Order By: Relevance
“…In the present study, we identified the deregulation of miR-106a in ovarian cancer. miR-106a is widely expressed in diverse human tumors, including gastric, non-small cell lung, pancreatic, colorectal and ovarian cancer (6,8,9,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified the deregulation of miR-106a in ovarian cancer. miR-106a is widely expressed in diverse human tumors, including gastric, non-small cell lung, pancreatic, colorectal and ovarian cancer (6,8,9,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] miR-106a posttranscriptionally regulates the expression of interleukine-10 (IL-10), which is a key modulator of the immune system. On the other hand, miR-106a expression is regulated by tumor necrosis factor alpha and lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated angiogenesis, dominated by immature and leaky blood vessels, is known to be highly dependent on VEGF-A as an EC survival factor (11)(12)(13), and patients with low miR126 expression may consequently benefit the most from the addition of anti-VEGF-A. A possible prognostic value of miR126 in mCRC has been proposed as well (9,10,14).…”
Section: Introductionmentioning
confidence: 99%